Platonic Curriculum and the Allegory of the Cave - David Rybák (Theology and Philosophy of Education, 2022)
The following paper attempts to show and take into account in basic terms the unity and direction of the movement of education as presented in Plato’s Republic. We show that education, according to Plato, essentially involves a claim to knowledge in the sense of understanding what is valid regardless of space and time and acting on the basis of norming oneself by this understanding. Then, namely, in the sense of this distinction, an educated person is one who is able to distinguish the important and the unimportant in his knowledge and in his life.